Analisis Kemampuan Mahasiswa Matematika FMIPA Unimed dalam Menyelesaikan Permasalahan Konvergensi dan Divergensi Barisan Bilangan Real dengan Berbantuan Software MATLAB - Cecilia Br Perangin Angin; Combest Prajogo Tambunan; Raja Harly Anugrah Lubis; Usnul Marisa Siregar; Yumna Khairi Amani Piliang (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to analyze the ability of FMIPA Mathematics students at Medan State University (Unimed) in solving problems of convergence and divergence of real number sequences, as well as evaluating the effectiveness of using MATLAB software in supporting understanding of these concepts. This research is based on the aim of overcoming students' difficulties in understanding the concepts of convergence and divergence. The research method used was qualitative, with a sample of 20 students selected using purposive sampling. Data was collected through written tests and observations of the use of MATLAB which were distributed via Google Form in solving questions. The results show that 55% of students are in the